Performance, Heterochrony, Historiography: The Wooster Group’s 2007–2009 Production of Busenello/Cavalli’s La Didone (1641) and Baroque Opera Representation - Calcagno, Mauro (Schweizer Jahrbuch für Musikwissenschaft, 2026)
The article investigates how the staging of Baroque operas in contemporary performances across Europe and the United States engages with temporal and historiographical concerns. It focuses on the Wooster Group's experimental production of Francesco Cavalli's La Didone, which took place between 2007 and 2009 in Brussels, Rotterdam, Edinburgh, New York, Luxembourg City, and Los Angeles. By contrasting this benchmark production with traditional reconstructionist and modern Regietheater approaches, the article highlights key contradictions in today’s representation of Baroque opera, such as the tension between sonic and visual elements and between historical and contemporary acting styles. The Wooster Group’s intermedial production adopts a heterochronic, non-linear approach, integrating live performance with simultaneous reenactments of Mario Bava’s sci-fi film Planet of the Vampires (1965). This multi-layered strategy challenges conventional ideas of representation in operatic stagings by blending historical and modern elements, live and mediated performance, and linear and non-linear timelines. Through an analysis of specific scenes, the article demonstrates how these strategies produce dialectical images (Benjamin) that destabilize distinctions between past and present while offering an innovative interpretation of Baroque opera. The article concludes that the Wooster Group’s approach can be interpreted as ‘postdramatic’ (Lehmann), providing an alternative paradigm to traditional operatic productions and their differing historiographical implications.